Product Quality, Brand Image, and Product Taste on Customer Trust at Arabica Coffee in Bandung - Zulki Zulkifli Noor (Dinasti Publisher, 2024)
This study investigates the influence of product quality, brand image, and product taste on customer trust in Arabica coffee in Bandung. With the rising popularity of coffee consumption in the region, understanding the factors that drive customer trust is crucial for maintaining competitiveness in the coffee industry. Data was collected from Arabica coffee consumers through a structured survey, and analyzed using multiple regression analysis. The results indicate that all three factors—product quality, brand image, and product taste—positively and significantly affect customer trust. These findings suggest that Arabica coffee producers should focus on enhancing these attributes to foster stronger customer relationships and loyalty. The study contributes to the literature on customer behavior in the specialty coffee market and provides actionable insights for businesses to improve customer trust.